Frequency of significant steatosis and compensated advanced chronic liver disease among adults with chronic liver disease - Shahrani, Shahreedhan; Singh Gill, Sandeep; Sooi, Choong Yeong; Skantha, Ruben; Chandra Kumar, C. Vikneshwaran; Limun, Mohd Fairul; Nik Muhamad Affendi, Nik Arsyad; Chuah, Kee Huat; Khoo, Stanley; Rajaram, Ruveena Bhavani; Chan, Wah Keong; Mahadeva, Sanjiv (John Wiley & Sons Australia, 2023)
Background: With changes in the epidemiology and treatment of chronic liver disease (CLD), the impact of various etiologies of liver disease on steatosis and advanced fibrosis are uncertain.